Bimbingan Program Keputrian dalam Membentuk Religiusitas pada Disabilitas Netra (Jurnal Wahana Konseling, 2024)
The purpose of this study is to explore and analyze the implementation of the women's program as a means of forming religiosity in the beneficiaries of girls with visual disabilities at the Bhakti Candrasa Netra Disability Social Service House in Surakarta, Central Java. Qualitative method with phenomenological approach. Data were obtained through in-depth interviews with three female beneficiaries and two social workers. Data analysis was carried out through data reduction, data presentation, and conclusion drawing. Source triangulation was used to ensure the accuracy of the data. The results showed that the women's program was effective in increasing Islamic religious knowledge, developing a love for the Qur'an, and improving the quality of worship of the female beneficiaries. The learning methods used include lectures, Q&A, and discussions, with an emphasis on sensory-based learning, the use of Braille Quran, interactive media, experiential learning, Islamic-based character education, and psychosocial support. The program also has an impact on a deeper understanding of religious values and the application of religious practices in daily life. The women's program at RPS Bhakti Candrasa Surakarta is effective in shaping religiosity in female beneficiaries with visual disabilities, so that they can adjust to society with strong beliefs and behavior in accordance with Islamic teachings.